Analisis Kinerja Sistem Pengendali Kursi Roda Elektrik Berbasis Pulse Width Modulation (PWM) terhadap Variasi Beban dan Evaluasi Penggunaan Energi - Daniel Akhyar; Faizil Al Aqsa; M. Yusuf; Ari Afrizal (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
The aim of this research is to determine the effect of different PWM values on speed, current, power, and energy consumption of the wheelchair under various loads. The system was developed using an Arduino Uno as the main controller, a joystick for direction and speed control, an ultrasonic sensor to detect obstacles, and DC motors as the actuators. Tests were conducted with load variations ranging from 40 kg to 80 kg and PWM values from 40 to 120. The test results show that as the PWM value increases, the wheelchair’s speed also increases, but energy consumption rises accordingly. However, within the PWM range of 80 to 100, the system operates most efficiently since energy consumption does not increase significantly compared to the gain in speed. Based on these findings, the PWM-based electric wheelchair control system is considered effective, efficient, and stable under varying load conditions, making it a promising approach for the design of energy-efficient automatic wheelchairs.